-2(4x-9)=10

Simple and best practice solution for -2(4x-9)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4x-9)=10 equation:


Simplifying
-2(4x + -9) = 10

Reorder the terms:
-2(-9 + 4x) = 10
(-9 * -2 + 4x * -2) = 10
(18 + -8x) = 10

Solving
18 + -8x = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + -8x = 10 + -18

Combine like terms: 18 + -18 = 0
0 + -8x = 10 + -18
-8x = 10 + -18

Combine like terms: 10 + -18 = -8
-8x = -8

Divide each side by '-8'.
x = 1

Simplifying
x = 1

See similar equations:

| 12x-4+x=180 | | 9d^2+3d-5=0 | | 8(3m-2)=104 | | 41=6v-7 | | 42y-42y^2=20 | | (2x-1)(x+2)+(3x+1)(x-1)= | | 3(n+4)-8=11-(6-2n)52 | | 3*(2x-1)=9 | | 8x-2y=60 | | 7/(10x)=103/20 | | 4x=8x+32 | | x-0.7=5.5 | | 7x3/6 | | x*2x=50000 | | 3(2b-1)=27 | | 1/8x-1/8y=19 | | log(12)2+log(12)x=log(12)(x+7) | | 2x^3+12=0 | | -7-13=15 | | -4x+2y=34 | | 2x+7=-3x+8 | | (4x+7)=(7x-8) | | (6a^4b^3)(3ab^2)= | | X-4+12=12-2 | | 6xy*xy*4y= | | 2(4y-2)= | | (x+3)+(x-3)=1 | | (x+3)+(x-3)=0 | | 6(y+9)-56= | | 3x+11y=-7 | | 4+3x=32 | | 2/x=1/4 |

Equations solver categories